Health Counseling About Prevention of Diarrhea at Elementary School 25 of Bima City - Eti Noviatul Hikmah; Yati Purnama (LPPM Sekolah Tinggi Teknologi Nusantara Lampung, 2023)
Community service through health education for children regarding the prevention of diarrhoea in elementary school children is vital so that children can prevent the emergence of diarrheal diseases in children, especially in the school environment. The incidence of diarrhoea in Indonesia is around 200–400 cases per 1000 people yearly. The incidence of diarrhoea in Indonesia is 60 million annually, and 80% are children. Health education is crucial to do in order to increase elementary school children's knowledge about diarrhoea prevention in the elementary school environment in Kota Bima, especially the children of SDN 25 Kota Bima. Based on the preliminary studies that have been carried out, the number of children who know about preventing diarrhoea in children is 4 out of 10 children. The aim is to conduct counselling on preventing diarrhoea in children so that Indonesia is free from diarrheal diseases, especially in early childhood. The activity method is carried out by making pre- and post-test questions to measure the level of knowledge before and after being given counselling. Based on the results of the assessment before (pretest), counselling was given; namely, 21 children with less knowledge (70%) had sufficient knowledge of 9 people (30%). Furthermore, experienced an increase after counselling was carried out by conducting a reassessment (post-test) where children who had less knowledge, namely 5 people (16.7%), 15 people (50%) were good, and 10 people (33.3%) were good.